Opportunities and Challenges of Automation Experience by some Academic Libraries in Anglophone sub-Saharan Africa : a Perspective on West Africa - Underwood, Peter G. (University of Pretoria, 2016)
Mini Dissertation (MIT)--University of Pretoria, 2015.